Psychological Assistance in Managing Anxiety Among Jambi SMEs - Risnawaty, Widya; Salsabila, Afra; Hidayah, Nurul (Journal of Innovation and Community Engagement, 2022)
The pandemic caused by Covid-19 virus has brought various impacts to the Indonesian people, including the people of Jambi, especially in the economic and social fields. The PPKM (Enforcement of Restriction on Community Activities) that was implemented made adversity to Jambi residents, especially Jambi SMEs (Small to Medium Enterprises) who feel the impact. Their income has decreased. The spread of the Covid-19 virus caused some participant to experience anxiety, from mild to severe. This activity was intended to provide special psychological assistance to Jambi SMEs participants who experience anxiety. There were 4 participants who experienced anxiety. Implementation methods include psychoeducation, relaxation technique exercise and group counseling with Cognitive Behavior Therapy – Recovery Oriented (CT-R) approach. The results of psychoeducation showed an increase in the score from pretest to posttest by 22.5%. Relaxation exercises succeeded in reducing anxiety levels in most of the participants. In group counseling activities with the CT-R approach, each participant managed to find his adaptive ability again.